If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(x + -1)(x + -3)(x + -6) = 0 Reorder the terms: (1 + x)(x + -1)(x + -3)(x + -6) = 0 Reorder the terms: (1 + x)(-1 + x)(x + -3)(x + -6) = 0 Reorder the terms: (1 + x)(-1 + x)(-3 + x)(x + -6) = 0 Reorder the terms: (1 + x)(-1 + x)(-3 + x)(-6 + x) = 0 Multiply (1 + x) * (-1 + x) (1(-1 + x) + x(-1 + x))(-3 + x)(-6 + x) = 0 ((-1 * 1 + x * 1) + x(-1 + x))(-3 + x)(-6 + x) = 0 ((-1 + 1x) + x(-1 + x))(-3 + x)(-6 + x) = 0 (-1 + 1x + (-1 * x + x * x))(-3 + x)(-6 + x) = 0 (-1 + 1x + (-1x + x2))(-3 + x)(-6 + x) = 0 Combine like terms: 1x + -1x = 0 (-1 + 0 + x2)(-3 + x)(-6 + x) = 0 (-1 + x2)(-3 + x)(-6 + x) = 0 Multiply (-1 + x2) * (-3 + x) (-1(-3 + x) + x2(-3 + x))(-6 + x) = 0 ((-3 * -1 + x * -1) + x2(-3 + x))(-6 + x) = 0 ((3 + -1x) + x2(-3 + x))(-6 + x) = 0 (3 + -1x + (-3 * x2 + x * x2))(-6 + x) = 0 (3 + -1x + (-3x2 + x3))(-6 + x) = 0 (3 + -1x + -3x2 + x3)(-6 + x) = 0 Multiply (3 + -1x + -3x2 + x3) * (-6 + x) (3(-6 + x) + -1x * (-6 + x) + -3x2 * (-6 + x) + x3(-6 + x)) = 0 ((-6 * 3 + x * 3) + -1x * (-6 + x) + -3x2 * (-6 + x) + x3(-6 + x)) = 0 ((-18 + 3x) + -1x * (-6 + x) + -3x2 * (-6 + x) + x3(-6 + x)) = 0 (-18 + 3x + (-6 * -1x + x * -1x) + -3x2 * (-6 + x) + x3(-6 + x)) = 0 (-18 + 3x + (6x + -1x2) + -3x2 * (-6 + x) + x3(-6 + x)) = 0 (-18 + 3x + 6x + -1x2 + (-6 * -3x2 + x * -3x2) + x3(-6 + x)) = 0 (-18 + 3x + 6x + -1x2 + (18x2 + -3x3) + x3(-6 + x)) = 0 (-18 + 3x + 6x + -1x2 + 18x2 + -3x3 + (-6 * x3 + x * x3)) = 0 (-18 + 3x + 6x + -1x2 + 18x2 + -3x3 + (-6x3 + x4)) = 0 Combine like terms: 3x + 6x = 9x (-18 + 9x + -1x2 + 18x2 + -3x3 + -6x3 + x4) = 0 Combine like terms: -1x2 + 18x2 = 17x2 (-18 + 9x + 17x2 + -3x3 + -6x3 + x4) = 0 Combine like terms: -3x3 + -6x3 = -9x3 (-18 + 9x + 17x2 + -9x3 + x4) = 0 Solving -18 + 9x + 17x2 + -9x3 + x4 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 6=-9-6 | | 51-7x=12+(-4x) | | 2x+3+5x=13 | | 5+3(n+9)=-3 | | 5+x-3[x+4]=-17 | | f(x)=2x+x-1 | | 3n-13=n+6 | | (x+5)(x-5)(x-7)=0 | | x^2+8x-7=8 | | 16x+18y+10x-7y= | | 5y^2+8y= | | 3k-2=39 | | 5X^3/(10x^2+5x) | | 5=-5+2x | | -x+3x-9=5 | | 9x+6-8=-38 | | 4x-3+2x+5=20 | | 15/2=5w | | 5x^3/10x^2+5x | | 5.00+0.8x=14.6 | | 5+8x=14.6 | | 3(10+-2y)+4y=8 | | 3-(4b-2)=3-4b-2 | | -4x-3=-6x-9 | | (8-x)+4=0 | | 5x+646464646464644646464646464644664464646464645554987604596=3 | | m^2-8m+16/5m^2+m | | 10+3x=2x-8x+40 | | y=-0.25x | | -12=39-6 | | x+2-9102301+78xypn-9087px=-12123 | | y=-0.25 |